Long Term Echocardiographic Follow up of Percutaneous Transvenous Mitral commissurotomy (PTMC) - Jan, Hikmat Ullah; Hassan, Mahmood ul; Hafizullah, Muhammad (Journal of Postgraduate Medical Institute, 2011)
This study was conducted to report the local experience of long term echocardiographic follow up of percutaneous transvenous Mitral Commissurotomy in symptomatic severe mitral stenosis (MS) patients. We conducted this retrospective computer data base echocardiographic study of symptomatic severe MS patients (who underwent PTMC from 1992 to 1995 in our cardiology unit) to evaluate the immediate and long term echocardiographic results of PTMC in 269 patients. We did transthorasic and transoesophageal echocardiographic study of all symptomatic severe mitral stenosis patients. Those patients who were found eligible and underwent PTMc were selected for the study. Total of 269 patients were evalauted. The study shows that PTMC is an effective and safe methods to relieve MS and it improves the haemodynamics and the results are sustained over prolonged period.